Circular RNA-0007059 protects cell viability and reduces inflammation in a nephritis cell model by inhibiting microRNA-1278/SHP-1/STAT3 signaling - Peng-Wei Guo; Hai-Ting Huang; Jing Ma; Yao Zuo; Dan Huang; Lin-Lin He; Zi-Ming Wan; Cheng Chen; Fa-Fen Yang; Yan-Wu You (BMC, 2021)
Abstract Background Increasing evidence has indicated that circular RNAs (circRNAs) play a role in various diseases. However, the influence of circRNAs in nephritis remains unknown. Methods Microarray analysis and RT-qPCR were used to detect the expression of circRNA. Type I IFN were administrated to RMC and HEK293 cells to establish a nephritis cell model. CCK-8, MTT assay, and flow cytometry were used to assess cell proliferation, viability, and apoptosis of cells. Bioinformatics analysis and dual luciferase reporter assay detect the interaction of circ_0007059, miRNA-1278, and SHP-1. Glomerulonephritis was performed in a mouse model by administration of IFNα-expressing adenovirus. IHC staining showed the pathogenic changes. Results In the present study, the expression of circ_0007059 in type I interferon (IFN)-treated renal mesangial cells (RMCs), lupus nephritis (LN) specimens, and HEK293 cells was downregulated compared with that in normal healthy samples and untreated cells. Circ_0007059 overexpression resulted in increased cell proliferation, cell viability, apoptosis, and inflammation-associated factors (CXCL10, IFIT1, ISG15, and MX1) in RMCs and HEK293 cells. In addition, circ_0007059 overexpression significantly restored cell proliferation and viability and inhibited IFN-induced apoptosis. Further, the increased expression resulted in reduced inflammation and the downregulation of CXCL10, IFIT1, ISG15, and MX1 in RMCs and HEK293 cells. Circ_0007059 serves as a sponge for miR-1278 so that the latter can target the 3'-untranslated region of SHP-1. Overexpressed circ_0007059 inhibited miR-1278 expression and elevated SHP-1 expression, subsequently reducing STAT3 phosphorylation. Meanwhile, miR-1278 was upregulated and SHP-1 was downregulated in LN samples and IFN-treated cells. The restoration of miR-1278 counteracted the effect of circ_0007059 on viability, apoptosis, and inflammation as well as on SHP-1/STAT3 signaling in RMCs and HEK293 cells. We also investigated the role of SHP-1 overexpression in IFN-treated RMCs and HEK293 cells; SHP-1 overexpression resulted in a similar phenotype as that observed with circ_0007059 expression. Conclusions The study indicates that circ_0007059 protects RMCs against apoptosis and inflammation during nephritis by attenuating miR-1278/SHP-1/STAT3 signaling.